Spremembe etnične in migracijske ter izobrazbene strukture prebivalstva mestne občine Ljubljana - primerjava podatkov popisov 1991, 2002 in 2015 - Josipovič, Damir (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2019)
The article deals with the comparison of the censuses of 1991, 2002, and 2015 data. It analyzes the changes of ethnic, migration and educational structure of the Urban Municipality of Ljubljana. While stating that the classical analysis of the data on ethnicity, language, and religion within the census data is not possible any more, the author presents the application of migration analysis in order to surmise the changes in ethnic structure. Moreover, the article applies the complex analysis of assessing the differences in educational attainment of population in Ljubljana. Analysis showed that the Urban municipality of Ljubljana changed considerably as regards migration or socio-economic characteristics. The processes of pronounced gentrification on one hand were coupled pauperisation on the other, with the latter being especially characteristic for the migrant population.
Keywords: družbeno razslojevanje; etnična pripadnost; mestna občina Ljubljana; migracije; narodna pripadnost; priseljenci